2022
DOI: 10.3389/fphar.2022.896920
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways and Roles for Vitamin K2-7 as a Health-Beneficial Nutraceutical: Challenges and Opportunities

Abstract: Vitamin K2-7, also known as menaquinone-7 (MK-7) is a form of vitamin K that has health-beneficial effects in osteoporosis, cardiovascular disease, inflammation, cancer, Alzheimer’s disease, diabetes and peripheral neuropathy. Compared to vitamin K1 (phylloquinone), K2-7 is absorbed more readily and is more bioavailable. Clinical studies have unequivocally demonstrated the utility of vitamin K2-7 supplementation in ameliorating peripheral neuropathy, reducing bone fracture risk and improving cardiovascular hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 127 publications
0
13
0
1
Order By: Relevance
“…The association of VitK2 involvement in the repression of pathological vascular calcification and the upregulation of Gas6 expression has been shown (Jadhav et al, 2022;Jiang et al, 2016). In a study conducted by Qiu et al (2017) Western blotting detected that substantial aortic smooth muscle Gas6 expression was restored after VitK2 treatment and that a significant decrease of VSMC calcification and apoptosis induced by CaCl 2 and β-sodium glycerophosphate was also observed.…”
Section: Calcification Modulated By Gas6mentioning
confidence: 99%
“…The association of VitK2 involvement in the repression of pathological vascular calcification and the upregulation of Gas6 expression has been shown (Jadhav et al, 2022;Jiang et al, 2016). In a study conducted by Qiu et al (2017) Western blotting detected that substantial aortic smooth muscle Gas6 expression was restored after VitK2 treatment and that a significant decrease of VSMC calcification and apoptosis induced by CaCl 2 and β-sodium glycerophosphate was also observed.…”
Section: Calcification Modulated By Gas6mentioning
confidence: 99%
“…Clinical evidence demonstrates that K2-7 dietary supplementation can ameliorate peripheral neuropathy, reduce bone fracture risk, and improve cardiovascular health [53 ▪ ]. The mechanistic basis for K2-7 might be mediated through signal transduction pathways including PI3K/AKT, MAP kinase, JAK/STAT, NF-κB, and through suppression of proinflammatory mediators IL-1α, IL-1β, and TNF-α [58 ▪ ]. A case report showed that vitamin K deficiency can result in permanent peripheral neuropathy in infants with biliary atresia [59].…”
Section: Vitamin Kmentioning
confidence: 99%
“…La vitamina K2 contribuye a la salud ósea y cardiovascular, siendo la menaquinona-7 (MK-7) la que se absorbe de manera más eficiente y exhibe la mayor biodisponibilidad, volviéndose popular como suplemento para la salud ósea y vascular (Sato et al, 2012). La vitamina K2-7, también conocida como menaquinona-7 (MK-7) es una forma de vitamina K que tiene efectos beneficiosos para la salud en la osteoporosis, las enfermedades cardiovasculares, la inflamación, el cáncer, la enfermedad de Alzheimer, la diabetes y la neuropatía periférica en humanos (Jadhav et al, 2022). MK-7 sirve como cofactor en el proceso de carboxilación de ciertos residuos de glutamato unidos a proteínas, donde estos se convierten en residuos de -carboxiglutamato (Gla).…”
Section: Funcionesunclassified